PENGARUH TEMAN SEBAYA DAN PRESTASI BELAJAR EKONOMI TERHADAP PERILAKU KONSUMSI SISWA SMA KHADIJAH SURABAYA - Hadija, Lisa (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
This study aimed to determine influences of peer and economics learning achievement on students consumption behavior. This study is explanatory research using a quantitative approach. The population covers 192 students of grade X at Khadijah Senior High School of Surabaya. Samples are 130 students which determined by using simple random sampling technique, with Slovin formula. The data were collected using questionnaires and documentation. The data were analyzed quantitatively using simple and multiple linear regression. The hypothesis was tested using the t test technique and F test with the help of SPSS software. Based on the research results, it was concluded that: (1) There is a partial significant influence of peer on students consumption behavior. (2) There is a partial influence of economics learning achievement on students consumption behavior, and (3) There are simultaneous significant influences of peer and economics learning achievement on students consumption behavior.